Theoretical conceptions about the creativity and its development in the teaching-learning process - Yudelqui Martínez León; Modesta Moreno Iglesias; Ania Teresa Cordero González (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2016)
The creativity has been and it is object of study of several disciplines, like: Psychology, the Sociology, Epistemology, as well as Philosophy, all they research it from their own conceptual-methodological specificity, and there are big polemic current to determine its limits, what can constitute an obstacle for the researchers, hence the necessity to clear up and specify the theoretical-methodological framework from which this process is researched. The present work approaches a topic of great value when appealing to the means and methods that are sustained in the highest analysis levels on the learning with creative focus, it begins with a valuation of the creativity importance like essential process in the development of the teaching learning process, where the elements that constitute theoretical bases for its improvement are specified. The research has the purpose of offering a systematization of the main theoretical referents that sustain the creativity, deepening in its dimensions and indicators with didactic objectives to increase the learning quality. There was used a system of investigative methods of theoretical, empiric and statistical levels that allowed to verify the existent problematic situation in relation to the development of the creativity. The offered theory allows the design of new strategies to improve the teaching-learning process, locating the student like the main character of his/her own learning.